MODERN VIEW ON DIFFERENT KINDS OF BOWEL PREPARATION FOR ELECTIVE COLORECTAL SURGERY - A. Yu. Olkina; A. S. Petrov; L. L. Panaiotti; A. М. Karachun; T. S. Lankov (Сибирский онкологический журнал)
Purpose: to assess current data on the effect of different approaches to preoperative bowel preparation before elective colorectal surgery on short-term treatment outcomes.Material and Methods. Online system PubMed of U.S. National Library of Medicine was used to find articles with key words “mechanical bowel preparation”, “surgical site infection”, “oral antibiotics”. A total of 226 articles were reviewed. 31 articles were selected for final review. Furthermore, ClinicalTrials.gov site was used to find actual and recruiting trials.Results. Mechanical bowel preparation (MBP) used to be a standard procedure for a long time. Nowadays, routine use of MBP seems to be debatable. Alternative approaches, e.g. absolutely no preparation or the use of MBP in combination with oral antibiotics, are considered. Data on performing different kinds of bowel preparation is reviewed in this article.Conclusion. Optimal approach of preoperative bowel preparation is still questionable. Combination of mechanical bowel preparation and oral antibiotics seems to be a preferable method. However, there is not enough evidence to exclude anothertechniques. It’s required to conduct additional randomized controlled trials.